Exploring Functional Redundancy in the Immunoglobulin μ Heavy-Chain Gene Enhancer - Dang, Wei (American Society for Microbiology, 1998)
Immunoglobulin (Ig) μ heavy-chain gene enhancer activity is mediated by multiple DNA binding proteins. Mutations of several protein binding sites in the enhancer do not affect enhancer activity significantly. This feature, termed redundancy, is thought to be due to functional compensation of the mutated sites by other elements within the enhancer. In this study, we identified the elements that make the basic helix-loop-helix (bHLH) protein binding sites, μE2 and μE3, redundant. The major compensatory element is a binding site for interferon regulatory factors (IRFs) and not one of several other bHLH protein binding sites. These studies also provide the first evidence for a role of IRF proteins in Ig heavy-chain gene expression. In addition, we reconstituted the activity of a monomeric μ enhancer in nonlymphoid cells and defined the domains of the ETS gene required for function.